Influence of spirulina platensis on growth performance of weanling pigs - Grinstead, G.S.; Sawyer, J.; Maxwell, K.; Stott, R.; Moser, A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We conducted three experiments to evaluate the influence of an algal feed additive, Spirulina platensis, on weanling pig performance. Two experiments conducted under commercial production conditions indicated a response to Spirulina platensis in meal-based diets but not pelleted diets. Another experiment concluded that Spirulina platensis tended to improve F/G early in the trial but not for cumulative performance. Results of these three experiments suggest that Spirulina platensis added at low inclusions to the diet may enhance performance. However, the results lacked consistency across experiments and warrant further investigation.
Keywords: Swine; Starter pigs; Algae; Performance